2007
DOI: 10.1111/j.1524-4725.2007.33117.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Excision versus Curettage plus Cryosurgery in the Treatment of Basal Cell Carcinoma

Abstract: These data reflect the outcome of the first randomized controlled trial with long-term follow-up in the treatment of BCC, comparing C&C with SE. Although not statistically significantly different, the observed differences could still be of clinical relevance. Owing to the trend toward lower recurrence rates, better cosmetic results, and reduced wound healing time, we believe that SE should be preferred to C&C in the treatment of primary, nonaggressive BCC of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 38 publications
3
37
1
4
Order By: Relevance
“…24,54 Due to generally poorer treatment outcomes when compared with surgical excision, cryosurgery for treatment of primary head and neck lesions or high-risk BCC is not generally indicated unless thermocouples are used to document tissue temperature and the physician has extensive training/experience with the technique. 55,56 Curettage is often combined with cryosurgery, which may improve cure rates relative to cryosurgery alone. 57 …”
Section: Cryosurgerymentioning
confidence: 99%
“…24,54 Due to generally poorer treatment outcomes when compared with surgical excision, cryosurgery for treatment of primary head and neck lesions or high-risk BCC is not generally indicated unless thermocouples are used to document tissue temperature and the physician has extensive training/experience with the technique. 55,56 Curettage is often combined with cryosurgery, which may improve cure rates relative to cryosurgery alone. 57 …”
Section: Cryosurgerymentioning
confidence: 99%
“…40 Moreover, EDC has been associated with inferior cosmetic outcome compared to excisional treatments. 46 Imiquimod has been touted as a relatively inexpensive, nonsurgical treatment for NMSC. 47 However, this treatment also has many limitations to its general use.…”
Section: Discussionmentioning
confidence: 99%
“…3 Multiple RCTs comparing standard surgical excision of BCC with topical medical therapy, C&E, photodynamic therapy (PDT), cryotherapy, radiation therapy, and MMS have been published. 32,[34][35][36][37][38][39] All the studies consistently reported low recurrence rates after standard excision of BCC with predominantly nonaggressive histologic growth patterns. Excision of nodular or superficial BCC with 3-to 4-mm margins in low-risk anatomic locations was associated with 2% to 4% recurrence rates after 3 to 5 years.…”
Section: Standard Excisionmentioning
confidence: 94%
“…35,[38][39][40] In a study comparing standard excision with C&E followed by cryosurgery for nonaggressive BCC on the head and neck, the 5-year recurrence rates were 8.2% and 17.6%, respectively. 36 Recurrence rates following surgical excision were uniformly significantly lower than those following treatment with topical therapy, radiation therapy, or destructive modalities. Only MMS was superior to standard excision for the treatment of primary and recurrent facial BCC after 5-and 10-years of follow-up.…”
Section: Standard Excisionmentioning
confidence: 97%